Business Terms With Multiple Words (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Terminology can be mentioned as one of the essential parts of linguistics to research lexemes in all spheres. The purpose of the article is to discuss business terms in linguistics as well as research some business terms with multiple words.